KAJIAN MUSIKOLOGI LAGU BELADON PADA KESENIAN MENDU DI KOTA PONTIANAK - Taufan E. P, Muhammad; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe Background in this research content was for created a documentary ofÂ Beladon Song on The Art of Mendu in Pontianak. General problems in this research were : How is the musical accompaniment of Beladon Song on The Art of Mendu in Pontianak description? The Purpose of this research was: 1) Described and denotated the Musical accompaniment and vocal of Beladon Song on The Art of Mendu in Pontianak, 2) Describing music form of Beladon Song on The Art of Mendu in Pontianak. The method that used in this research wasqualitative descriptive method and used musicology approach. The datas of this research were the result of the wich direct observation and interview to the informant about the System of Violin Melody, system of Gendang Panjang, Tawak and Vocal. The Data Analysis doing with the qualitive method, with the informant data, Jerie Anwar, Herman, Ilham Setiawan, S.Sn, and Yoga Kharisma, S.Pd who always active in artistic activity and know about the musical accompaniment of Beladon Song on The Art of Mendu in Pontianak. Keywords: Beladon Song, Mendu, Art of Mendu, Musicologue Study, Pontianak.